PEMETAAN KONTEN INFORMASI AKUN INSTAGRAM @PERPUSUINYOGYAKARTA - Risna Septi Harfiani; Nining Sudiar; Vita Amelia (Info Bibliotheca: Jurnal Perpustakaan dan Ilmu Informasi, 2023)
In this study examines an Instagram account @perpusuinyogyakarta. From this account the researcher collected uploads published by @perpusuinyogyakarta during January-December 2021. The purpose of this study was to find out what content was uploaded by the @perpusuinyogyakarta account and how the mapping of the Instagram account @perpusuinyogyakarta during January - December 2021 and what percentage. This study uses a quantitative descriptive method with a sample of 433 posts uploaded during January-December 2021 (1 year). Data collection techniques are observation and documentation study. The results showed that out of 433 posts of informational content and five indicators of library Instagram content, namely event indicators, internal indicators, speech indicators, library information indicators, and knowledge indicators. The most posted indicator is the indicator that shows information related to library information with 161 uploads or 39.07%, the second is information related to events or promoting events/activities with 88 uploads or 21.35%, the third is shows information related to speech with 78 uploads or with a percentage of 18.93%, the fourth is information that contains internal activities with 53 uploads or a total of 12.86%, and there is a low upload, namely information related to general knowledge or certain fields with 47 uploads or a total of 11.40%, and there is a follower response to content that is seen as quite active in the comments column which is communicative with the account manager @perpusuinyogyakarta such as comments that are praise or appreciation.